Happy Hosts? Hedonic and Eudaimonic Wellbeing in the Sharing Economy - von Richthofen, Georg (Frontiers in Psychology, 2022)
Sharing economy platforms mediate exchanges between service providers and consumers. The experiences of service providers in the sharing economy have been extensively studied. Nevertheless, our knowledge in regard to the extent to which providers’ participation influences their wellbeing remains incomplete. This study focuses on the peer-to-peer accommodation platform Airbnb and explores why and how different aspects involved in hosting can contribute to or hinder hosts’ hedonic and eudaimonic wellbeing. To that end, I conducted a netnography and depth interviews with Airbnb hosts. Based on a qualitative analysis of the overall dataset, I identify three sources of positive affect associated with hosting, namely, the sociability involved in the host-guest interaction, the act of providing hospitality, and positive feedback from guests. However, I also identify four conditions, which can turn hosting into a source of negative affect, namely, customer misbehavior, high volumes of guests, negative reviews, and income dependency. In addition, I elaborate on the relationship between hosting and life satisfaction in regard to the income that hosts generate through hosting and the working conditions of Airbnb hosts. Last but not least, I show that being a provider on Airbnb can contribute to (and in some cases hinder) eudaimonic wellbeing, focusing on four dimensions of eudaimonia, namely, self-realization, personal growth, a sense of purpose and meaning, and relationships. Theoretical and managerial implications for service providers and sharing economy platforms are discussed.